Clarissa Dalloway’s itinerary: narrative identity across texts - Monica LATHAM (E-REA)
This article sets out to examine the migration of Virginia Woolf’s character Clarissa Dalloway from its original score (The Voyage Out) to other autographic (the short story “Mrs Dalloway in Bond Street” and the novel Mrs Dalloway) and allographic (Robin Lippincott’s Mr Dalloway and John Lanchester’s Mr Phillips) texts. The itinerary selected here traces her evolution from the very beginning of the twentieth century, when she is a rather conventional character, to a modernist, then post-modernist and neo-modernist character at the beginning of the twenty-first century. This itinerary reflects the authors’ evolving literary theories on character representation and construction of fictional worlds. By following Clarissa Dalloway’s textual itinerary, this article provides insights into her narrative identities, that is to say the way the different authors perpetuate the original character’s diagnostic properties and adapt them to new diegetic environments. Clarissa Dalloway migrates across texts, mutating and adjusting to new socio-cultural concerns and aesthetic contexts.